The Whole Elephant : A Proposal for Integrating Cash, Accrual, and Sustainability-Gap Accounts - Irwin, Timothy (IMF Working Papers; Working Paper ;, 2015)
Although the budget deficit is much discussed in political debate and economic research, there is no agreement on how it should be measured. There are at least four options, which can be called the cash deficit, the financial deficit, the full-accrual deficit, and the comprehensive deficit. Each is informative, but each has problems of relevance or reliability. Some are more vulnerable to manipulation involving assets and liabilities that are unrecognized in the underlying accounting, others to manipulation involving the mismeasurement of recognized assets and liabilities. Governments should publish all four in a form that reveals their interrelationships.